(untitled) (Journal of Applied Oral Science, 2015)
Objective This in vitro study assessed the anti-erosive effect of experimental mouthrinses containing TiF4 and NaF on dentin erosive loss.Material and Methods Bovine dentin specimens were randomly allocated into the groups (n=15): 1) SnCl2/NaF/AmF (Erosion Protection®/GABA, pH 4.5, positive control); 2) experimental solution with 0.0815% TiF4(pH 2.5); 3) 0.105% NaF (pH 4.5); 4) 0.042% NaF+0.049% TiF4 (pH 4.4); 5) 0.063% NaF+0.036% TiF4 (pH 4.5); 6) no treatment (negative control). Each specimen was cyclically demineralized (Sprite Zero, pH 2.6, 4x90 s/day) and exposed to artificial saliva between the erosive challenges for 7 days. The treatment with the fluoride solutions was done 2x60 s/day, immediately after the first and the last erosive challenges of the day. Dentin erosive loss was measured by profilometry (μm). The data were analyzed using Kruskal Wallis/Dunn tests (p